Development and Feasibility of an Interactive Smartphone App for Early Assessment and Management of Symptoms Following Pancreaticoduodenectomy. Issue 3 (May 2019) - Gustavell, Tina; Langius-Eklöf, Ann; Wengström, Yvonne; Segersvärd, Ralf; Sundberg, Kay
Abstract : Background: Patients who have undergone pancreaticoduodenectomy because of pancreatic cancer experience distressing symptoms and unmet supportive care needs after discharge. To meet these needs, we have developed a mobile health app (Interaktor) for daily assessment of symptoms and access to self-care advice that includes a risk assessment model for alerts with real-time interactions with professionals. Objective: The study aim was to develop and test a version of the Interaktor app adapted for patients who have undergone pancreaticoduodenectomy. Methods: The app was developed and tested for feasibility in 6 patients during 4 weeks. One nurse monitored and responded to alerts. Logged data from the app were collected, and all participants were interviewed about their experiences. Results: Adherence to reporting daily was 84%. Alerts were generated in 41% of the reports. The patients felt reassured and cared for and received support for symptom management. The app was easy to use, had relevant content, and had few technical problems, although suggestions for improvement were given. Conclusions: The daily reporting of symptoms and having access to a nurse in real time in the case of an alarming symptom seem to enhance symptom management and render a feeling of security in patients. Some modifications of the app are needed before use in a larger sample. Implications for Practice: Daily reporting of symptoms after pancreaticoduodenectomy enhances symptom management, self-care, and participation without being a burden to patients, indicating that mobile health can be used in clinical practice by patients with poor prognosis who experience severe symptoms.